Redox-mediated synthesis of functionalised graphene: a strategy towards 2D multifunctional electrocatalysts for energy conversion applications - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Anothumakkool, Bihag; Kurungot, Sreekumar (ChemPlusChem, 2013)
A simple, one-step synthetic route for developing a two-dimensional multifunctional electrocatalyst is reported, by the functionalisation of graphene using oxidised ethylenedioxythiophene (O-EDOT). The mutually assisted redox reaction between graphene oxide (GO) and EDOT facilitates the reduction of GO to graphene with a concomitant deposition of O-EDOT on the surface of the graphene. The oxidised surface of GO catalyses the reaction without using an added reducing agent, so a controlled and uniform deposition of O-EDOT is ensured on the surface of graphene, which essentially prevents the restacking of the layers. UV/Visible, IR, Raman and X-ray photoelectron spectroscopy give valid evidence for the reduction and functionalisation of graphene sheets. The functional groups present on the surface of graphene are found to tune the physical and chemical properties of graphene. Consequently, the functionalised material displays enhanced electrocatalytic activity for the reduction of oxygen to water and I3- to I- relative to pristine graphene. These distinct property characteristics make the material a versatile cathode electrocatalyst for both alkaline anion-exchange membrane fuel cells and dye-sensitised solar cells.
Keywords: electrocatalysts; fuel cells; graphene; redox chemistry; solar cells